Learning how to manage by watching TV. Issue 2 (14th May 2018) - Towers, Ian
Abstract : Purpose: The transfer of management knowledge is usually seen as a formal process involving business schools, training courses and books. This paper aims to investigate the managerial content of TV drama programmes, considering the mechanisms that determine this and showing how this changes over time. The paper also shows how the content forms part of management discourse and how it may be used by viewers to understand what good and bad managers do and to modify their behaviour accordingly. Design/methodology/approach: Two links are discussed: between the economic system and cultural products and between cultural products and the individual. Police drama series are used as an example to show how current management practices are mediated through popular culture and how they are legitimised. Findings: The management styles and practices observed in police drama series have changed over the past 40 years to reflect the most recent trends. Bureaucratic management styles are shown in a negative light, whereas teamwork is shown positively. New trends such as the heavy use of consultants are also represented in recent programmes, providing evidence of how popular culture can make management practices part of managerial discourse. Originality/value: Films and TV programmes are analysed by management scholars, but usually to illustrate a particular theme. This paper does not take the managerial content as a given but identifies mechanisms through which it is determined and shows how it changes. Additionally, it shows the relationship between content and viewer. It provides evidence of the role of popular culture in the transfer of management knowledge and of how management related contents change over time.